Entrepreneurship Education and Digital Entrepreneurship as Drivers of Youth Employment and Social Impact in India: A Systematic Literature Review - Rajeev Sijariya; Prof. (Dr.) Prateek Agrawal; Dr. Nivedita Singh; Dr.Rinki Verma; Dr. Monika Singh; Dr. Rajneesh Khare; Dr. Ankita Gothwal (Journal of Advanced Research in HR and Organizational Management, 2026)
India is currently witnessing a profound demographic transition, where two-thirds of its population falls within the working-age group. If this young population is given the right skills, knowledge, chances, and access, it could be a great chance for the country to grow its economy, come up with new ideas, and change society. In this context, entrepreneurship is a major factor in creating jobs, promoting inclusive development, and keeping the economy stable. Entrepreneurship education helps people become successful entrepreneurs, and the rise of digital entrepreneurship creates opportunities for people with the right skills. All of these things are making people more likely to get jobs, start their own businesses, and make a positive difference in society. But current research on the main effects of entrepreneurship education and digital entrepreneurship is still spread out over many areas. This paper uses a systematic literature review (SLR) to look at how entrepreneurship education and digital entrepreneurship can help young people find jobs and improve their social lives in India. The paper adheres to PRISMA guidelines and systematically identified, screened, and analysed 36 peer-reviewed journal articles published from 2015 to 2025. The study contributes by integrating entrepreneurship education, digitalisation, and social impact perspectives within the Indian context and offers policy-relevant insights aligned with initiatives taken by the government, such as Digital India, Startup India, Atal Innovation Mission, and National Education Policy 2020. The findings of the research suggest that entrepreneurship education has a positive impact on entrepreneurial intentions and competence and generates employment for youth, while digital entrepreneurship broadens access to innovation opportunities and facilitates scalable business models. The digital revolution has built unprecedented opportunities for youth to venture into entrepreneurship that has increasingly contributed to social inclusion. This paper also suggests directions for future research and implications for educators and policymakers.